Study of substrate inhibition by electrophoretically mediated microanalysis in partially filled capillary - Papežová, Kateřina; Němec, Tomáš; Chaloupková, Radka; Glatz, Zdeněk (Journal of chromatography. A, Including electrophoresis and other separation methods, 2007)
Substrate inhibition is a common phenomenon in enzyme kinetics. We report here for the first time its study by a combination of the electrophoretically mediated microanalysis (EMMA) methodology with a partial filling technique. In this setup, the part of capillary is filled with the buffer best for the enzymatic reaction whereas, the rest of the capillary is filled with the background electrolyte optimal for separation of substrates and products. In the case of haloalkane dehalogenase, a model enzyme selected for this study, the enzymatic reaction was performed in 20 mM glycine buffer (pH 8.6) whereas 20 mM beta-alanine-hydrochloric acid buffer (pH 3.5) was used as a background electrolyte in combination with direct detection at 200 nm. The whole study was performed on poorly soluble brominated substrate--1,2-dibromoethane. As a result it was first necessary to find the compromise between the concentrations of the enzyme and the substrate preserving both the adequate sensitivity of the assay and at the same time the attainable substrate solubility. By means of the developed EMMA methodology we were able to determine the Michaelis constant (K(M)) as well as the substrate inhibition constant (K(SI)). The value of K(M) and K(SI) obtained were 7.7+/-2.5 mM and 1.1+/-0.4 mM, respectively. Observation of the substrate inhibition of haloalkane dehalogenase by 1,2-dibromoethane is in accordance with previous literature data.
Keywords: financování organizované; Sphingomonas; ethylendibromid; Financing, Organized; Ethylene Dibromide; Substrate Specificity; Kinetics; hydrolasy; mikrochemie; substrátová specifita; Electrophoresis, Capillary; Microchemistry; kinetika; Hydrolases; elektroforéza kapilární